Perceptions of urban residential landscapes: role of plants in enhancing outdoor thermal comfort - Mohd Yunos, Mohd Yazid; Md Saring, Md Zaidib (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
Urban residents satisfies the need for a place of environment is comfort and pleasant to live in. Otherwise, their quality of life may be affected. Human naturally tend to live in a comfort surrounding, and changes in environment features will effecting on human health, satisfaction and social context. Generally, outdoor thermal comfort problem occurred within urban area as compared to rural area. This situation happened due to the decreases of green area and green buffer within urban area. Understanding the occupants’ perceptions towards their living environment is critical for developing an effective development strategy. On the other hand public perception towards their outdoor environment is relatively underresearched, as the consequences there is great barrier isolate between climate science and public opinion. The aim of this paper, therefore, is to discuss public perception towards role of plants as a device to enhance outdoor thermal comfort level in urban terraced housing area in Malaysia. In addition, a questionnaire survey was conducted to evaluate occupants’ perceptions. The findings demonstrate great understanding and awareness among occupants regarding the important of plants in enhancing outdoor thermal comfort level and suggest adequate number of plants should be planted in adequate size of green area within terraced housing area. The finding is significant as the contribution to an understanding the potential of plant as a device in creating thermally comfortable housing environments in urban area